Perspektif Teologi Kristen tentang Kekerasan Seksual Terhadap Istri (Marital Rape) - Hutauruk, Destri Ayu Natalia; Aritonang, Delinda Elizabeth; Silitonga, Hamonangan (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2023)
Marital rape is a form of violence against women that hurts the victim. The church needs to be involved in dealing with this violence, and for this, there needs to be an exceptional theological basis regarding marital rape. This research aims to describe Christian theology regarding marital rape, especially in the context of Christian marriage. The research method used is a literature study. The research results show that marital rape is very contrary to the Christian concept of marriage, which is based on love. In love, there is no justification for violence in any form. It even teaches explicitly the husband's obligation to love his wife as Christ loves His church (Ephesians 5:25-28). Likewise, in 1 Corinthians 7:3-5, the Bible teaches that husbands and wives should fulfill each other's sexual needs, but only with mutual consent and consideration of each other's feelings.